2015
DOI: 10.1016/j.clnu.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of sorghum flour-containing pasta on plasma total polyphenols, antioxidant capacity and oxidative stress markers in healthy subjects: A randomised controlled trial

Abstract: The results demonstrated that pasta containing red wholegrain sorghum flour enhanced antioxidant status and improved markers of oxidative stress in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 32 publications
2
50
0
1
Order By: Relevance
“…In the present study, the antioxidant activity of sorghum IS 8525 was far higher than for the other genotypes ( Figs. Khan et al (2015) also found that durum pasta enriched with red sorghum flour had high levels of polyphenols and enhanced the antioxidant status and improved markers of oxidative stress in healthy human subjects compared with pastas made from durum alone. Additionally, in the present study HT significantly decreased the antioxidant activity of sorghum IS 8525 (Figs.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In the present study, the antioxidant activity of sorghum IS 8525 was far higher than for the other genotypes ( Figs. Khan et al (2015) also found that durum pasta enriched with red sorghum flour had high levels of polyphenols and enhanced the antioxidant status and improved markers of oxidative stress in healthy human subjects compared with pastas made from durum alone. Additionally, in the present study HT significantly decreased the antioxidant activity of sorghum IS 8525 (Figs.…”
Section: Resultsmentioning
confidence: 88%
“…A 2015 human clinical study reported that pasta containing red sorghum flour had high antioxidant activity in vitro and reduced biomarkers of oxidative stress in vivo after its consumption (Khan et al 2015). Polyphenols act as antioxidants, and much research has been carried out on their health benefits.…”
Section: Resultsmentioning
confidence: 99%
“…Their results indicated that the consumption of pasta enriched with lupin protein fractions reduced the rats’ body weight gain and food intake and decreased glycemia upon glucose overload trials. In a study involving 22 healthy human subjects, Khan and others () observed that the consumption of pasta enriched with 30% whole‐grain red sorghum flour enhanced antioxidant status and improved markers of oxidative stress. In contrast, the consumption of pasta enriched with whole‐grain white sorghum flour had no effect.…”
Section: Research Needsmentioning
confidence: 99%
“…A study has shown that consumption of pasta that incorporated red sorghum rather than white sorghum C 2019 Institute of Food Technologists ® Vol. 18, 2019 r Comprehensive Reviews in Food Science and Food Safety 2039 (low in phenolic compounds) significantly improved the health status in healthy people by increasing the plasma phenolic contents and antioxidant activity (Khan, Yousif, Johnson, & Gamlath, 2015). Also, sorghum can be very useful in muffin preparation, and muffins containing sorghum have been shown to have high resistant starch and slowly digestible starch contents (Poquette et al, 2014).…”
Section: Incorporating Sorghum Into Other Foodsmentioning
confidence: 99%